PERANCANGAN DAN IMPLEMENTASI JARINGAN FTTH GPON DI CLUSTER MARGA - Sastra, Bima; Diafari Djuni, IGAK; Ary Esta Dewi Wirastuti, Ni Made (Program Studi Teknik Elektro UNUD, 2024)
FTTH is an access network that uses fiber optic as a transmission medium to be distributed to customers. This fiber optic network has very good performance and is reliable and will have a very positive impact on customers, in order for clients to be happy with the services that telecom companies provide, especially in Indonesia. This research will discuss the design of a Fiber To The Home (FTTH) network in Tabanan Regency, Marga Village which includes the value of the Link Power Budget, Rise Time, and the amount of traffic required. after calculating the theoretical power link budget with samples based on the furthest distance (OLT to FAT 1). The value of the power receivers (Prx) from this design is obtained by a Prx value of -20.414 dBm (Downlink) and in the implementation the Prx difference is obtained, where at the farthest FAT (FAT 1) the Prx value is -16.65 dBm. Regarding the Marga area, it complies with the ITU-T G.984 standard, which is the GPON network implementation standard.